Olivine-norite rock detected by the lunar rover Yutu-2 likely crystallized from the SPA-impact melt pool. Issue 5 (14th November 2019) - Lin, Honglei; He, Zhiping; Yang, Wei; Lin, Yangting; Xu, Rui; Zhang, Chi; Zhu, Meng-Hua; Chang, Rui; Zhang, Jinhai; Li, Chunlai; Lin, Hongyu; Liu, Yang; et al.
Abstract: Chang'E-4 landed in the South Pole-Aitken (SPA) basin, providing a unique chance to probe the composition of the lunar interior. Its landing site is located on ejecta strips in Von Kármán crater that possibly originate from the neighboring Finsen crater. A surface rock and the lunar regolith at 10 sites along the rover Yutu-2 track were measured by the onboard Visible and Near-Infrared Imaging Spectrometer in the first three lunar days of mission operations. In situ spectra of the regolith have peak band positions at 1 and 2 μm, similar to the spectral data of Finsen ejecta from the Moon Mineralogy Mapper, which confirms that the regolith's composition of the landing area is mostly similar to that of Finsen ejecta. The rock spectrum shows similar band peak positions, but stronger absorptions, suggesting relatively fresh exposure. The rock may consist of 38.1 ± 5.4% low-Ca pyroxene, 13.9 ± 5.1% olivine and 48.0 ± 3.1% plagioclase, referred to as olivine-norite. The plagioclase-abundant and olivine-poor modal composition of the rock is inconsistent with the origin of the mantle, but representative of the lunar lower crust. Alternatively, the rock crystallized from the impact-derived melt pool formed by the SPA-impact event via mixing the lunar crust and mantle materials. This scenario is consistent with fast-cooling thermal conditions of a shallow melt pool, indicated by the fine to medium-sized texture (<3 mm) of the rock and the SPA-impact melting model [ Icarus 2012; 220 : 730–43].